The role of immune profile in predicting outcomes in cancer patients treated with immunotherapy - Botticelli, Andrea; Pomati, Giulia; Cirillo, Alessio; Scagnoli, Simone; Pisegna, Simona; Chiavassa, Antonella; Rossi, Ernesto; Schinzari, Giovanni; Tortora, Giampaolo; Di Pietro, Francesca Romana; Cerbelli, Bruna; Di Filippo, Alessandra; et al. (Frontiers in Immunology, 2022)
Background Despite the efficacy of immunotherapy, only a small percentage of pa-tients achieves a long-term benefit in terms of overall survival. The aim of this study was to de-fine an immune profile predicting the re-sponse to immune checkpoint inhibitors (ICIs). Methods Patients with advanced solid tumours, who under-went ICI treatment were enrolled in this prospective study. Blood samples were collected at the baseline. Thirteen soluble immune checkpoints, 3 soluble adhesion molecules, 5 chemokines and 11 cytokines were an-alyzed. The results were associated with oncological outcomes. Results Regardless of tumour type, patients with values of sTIM3, IFNα, IFNγ, IL1β, IL1α, IL12p70, MIP1β and TNFα below the median had longer overall survival (p<0.05). By using cluster analysis and grouping the patients according to the trend of the molecules, two clusters were found. Cluster A had a significantly higher mean progression free survival (Cluster A=11.9 months vs Cluster B=3.5 months, p<0.01), a higher percentage of disease stability (Cluster A=34.5% vs. Cluster B=0%, p<0.05) and a lower percent-age of disease progression (Cluster A=55.2% vs. Cluster B = 94.4%, p=0.04). Conclusion The combined evaluation of soluble molecules, rather than a single circulating factor, may be more suit-able to represent the fitness of the immune system status in each patient and could allow to identify two different prognostic and predictive outcome profiles.